DETERMINAN INTERNAL DIVIDEND PAYOUT RATIO PERUSAHAAN FARMASI TERDAFTAR DI BURSA EFEK INDONESIA - Zulkifli Zulkifli; Endri Endri; Augustina Kurniasih (University of Merdeka Malang, 2017)
This study aimed to examine and analyze the effect of the internal determinant of dividend payout ratio pharmaceutical company, annual data observation period 2008 until 2014. The type of this study was quantitative research. The population of the research was the entire pharmaceutical company consisting of 10 companies. The sampled criteria were pharmaceutical companies that consistently paid cash dividends. There were 6 companies listed in Indonesia Stock Exchange with non-probability sampling technique namely purposive sampling. Data analysis using panel data regression fixed effect which had larger R square value. The results showed that current ratio, return on assets, debt to equity ratio, earnings growth, return on equity, earnings per share and market to book value simultaneously were having significant influence to the dividend payout ratio. Partially return on assets and market to book value had a positive significant effect on the dividend payout ratio, while current ratio, debt to equity ratio and return on equity had a significant negative effect. Earnings growth and earnings per share did not have a significant influence on the dividend payout ratio. It was suggested to add external variables factors using more samples of companies.